Evaluation of computer based clinical decision support system and risk chart for management of hypertension in primary care: randomised controlled trial. Issue 7236 (11th March 2000) - Montgomery, Alan A; Fahey, Tom; Peters, Tim J; MacIntosh, Christopher; Sharp, Deborah J
Abstract: Objectives: To investigate the effect of a computer based clinical decision support system and a risk chart on absolute cardiovascular risk, blood pressure, and prescribing of cardiovascular drugs in hypertensive patients. Design: Cluster randomised controlled trial. Setting: 27 general practices in Avon. Participants: 614 patients aged between 60 and 79 years with high blood pressure. Interventions: Patients were randomised to computer based clinical decision support system plus cardiovascular risk chart; cardiovascular risk chart alone; or usual care. Main outcome measures: Percentage of patients in each group with a five year cardiovascular risk≥10%, systolic blood pressure, diastolic blood pressure, prescribing of cardiovascular drugs. Results: Patients in the computer based clinical decision support system and chart only groups were no more likely to have cardiovascular risk reduced to below 10% than patients receiving usual care. Patients in the computer based clinical decision support group were more likely to have a cardiovascular risk≥10% than chart only patients, odds ratio 2.3 (95% confidence interval 1.1 to 4.8). The chart only group had significantly lower systolic blood pressure compared with the usual care group (difference in means−4.6 mm Hg (95% confidence interval−8.4 to−0.8). Reduction of diastolic blood pressure did not differ between the three groups. The chart only group were twice as likely to be prescribed two classes of cardiovascular drugs and over three times as likely to be prescribed three or more classes of drugs compared with the other groups. Conclusions: The computer based clinical decision support system did not confer any benefit in absolute risk reduction or blood pressure control and requires further development and evaluation before use in clinical care can be recommended. Use of chart guidelines are associated with a potentially important reduction in systolic blood pressure.